A study on hr issues in retail outlets in coimbatore - M G, Saravanaraj; S, Arulsenthilkumar; N, Punitha (Journal of Management and Science, 2012)
Although retailing is a one of the very emerging fast growing sector in our country, Now massive retail stores has been functioning in the nook and corner of the all across the areas for fulfilling the customer needs under one roof Now, various well reputed organizations are very clear to setting up shop in India; they have a passion to be closer to the customer. At this time when the country‘s retail business is going through a transformation, there is a Compelling need for those involved in retailing and those who wish to be involved to understand this phenomenon systematically so that they can practice it perfectly.However one of the most problematic parts in the retail industry is that of acquiring, developing and etaining the personnel involved in the business of retail. This article has been undertaken to identify the pertinent HR issues faced in the retail sector, with a focus on retail outlets in Coimbatore. In this Study, afoundation to the aspect of retailing has been given, which includes Retailing in the global and Indian scenario, retail formats, etc. Then primary data has been collected with the help of a questionnaire, with the help of which the HR issues involved in retail have been identified. In the end suggestions and recommendations have been provided.